THE INHIBITION TEST OF RED POMEGRANATE (Punica granatum L.) PEEL EXTRACT AGAINST Staphylococcus aureus - Iin Eliana Triwahyuni; Novia Dyah Rahma Dhani; Leni Rokhma Dewi; Melok Aris Wahyukundari; Zainul Cholid; Dyah Setyorini (FKG Unlam, 2023)
Background: Staphylococcus aureus is a bacteria that commonly infects the oral cavity and linked to angular cheilitis. The most often used therapy for angular cheilitis is fusidic acid 2% cream, however it can cause urticaria, skin rashes, and irritation, thus an alternative is required to solve this issue. Pomegranate peel contains a variety of bioactive chemicals, including phenolics, which have antimicrobial activity. Purpose: To analyze the inhibition zone of red pomegranate peel extract at concentrations of 20%, 40%, 60%, and 80%, and determine the concentrations that have the greatest inhibition on the growth of Staphylococcus aureus. Method: The total phenolic content was measured using UV-Vis spectrophotometry method. The inhibition test was carried out by well-diffusion method with 6 sample groups, including positive control (2% fusidic acid), negative control (aquadest), and red pomegranate peel extract concentrations of 20%, 40%, 60%, and 80%. Results: Red pomegranate peel extract inhibited the growth of S. aureus at concentrations of 20%, 40%, 60%, and 80% with the inhibition zone diameter respectively 11.63 ± 0.88 mm, 13.84 ± 0.39 mm, 16.85 ± 0.58 mm, and 19.19 ± 0.43 mm Conclusion: Based on the results, red pomegranate peel extract at all concentrations have the capacity to inhibit the growth of S. aureus, with the highest concentration extract (80%) having the greatest inhibition. Keywords : Inhibition Test, Phenolic, Red Pomegranate Peel Extract, Staphylococcus aureus